Effect of Weed Attendance on Long Beans (Vigna sinensis L.) Productivity - La Sarido (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2018)
Long beans is one of the vegetable plants favored by the wider community, other than that the root nodules of this plant it capable to be a symbiosis with rhizobium bacteria to nitrogen fixationinto the soil so that the existence of nitrogen elements in the soil can be maintained, this is also accompanied by increased weed growth around the long beans so it will be affected the growth and yield of long beans crops.Research aimed to determine effect which caused by the existence of weeds on productivity of long beans (Vigna sinensis L.). Research was conducted on June 2016, North Sangatta Subs-district. The experiment was set up as a non factorial in a complete randomized block design which consists 5 blocks and 5 treatments, (P1) 100% weed existence, (P2) 75% weed existence, (P3) 50% weed existence (P4) 25% weed existenceand (P5) 0% weed existence. The Obtained results were analyzed by analysis of variance. The results showed that there was non significant on plant aged parameters when flowering 80%, plant aged at the time of first harvest and crop production, while the weight of fruit per plant was significantly. The best yielded when plant aged of 80% flowering on treatments of 100% weed existence and 25% weed existence i.e. 36,00 days;plant aged on the fastest harvest resulted ontreatments of 75, 25 and 0% weed existencei.e. respectively on 47and 20 days. Long beans has the the heaviest fruits were produced on the treatment of 0% weed existence i.e. 0,528 kg. While the heaviest production were produced on the treatment of 0%weed existence i.e.4,586 tonsha-1. Weeds that dominate on the planting area of long bean wereCyperus rotundus with the summed dominance ratio (SDR) 32,86%, there is decrease of production as 2,246% from total production if weed control is not done it.